Distinct thresholds govern Myc’s biological output in vivo - Daniel, J. Murphy (2008)
Deregulated Myc triggers a variety of intrinsic tumor suppressor programs that serve to restrain Myc’s oncogenic potential. Since Myc activity is also required for normal cell proliferation, activation of intrinsic tumor suppression must be triggered only when Myc signaling is oncogenic. However, how cells discriminate between normal and oncogenic Myc is unknown. Here we show that distinct threshold levels of Myc govern its output in vivo: low levels of deregulated Myc are competent to drive ectopic proliferation of somatic cells and oncogenesis but activation of the apoptotic and ARF/p53 intrinsic tumor surveillance pathways requires Myc over-expression. The requirement to keep activated oncogenes at low level to avoid engaging tumor suppression is likely an important selective pressure governing the early stages of tumor microevolution. SIGNIFICANCE Cancers are prevented by the activation of intrinsic tumor suppression programs that either fix the damage in cells or ensure that the damaged cells cannot propagate. Cancers can only arise once these tumor suppressor pathways are abrogated. Importantly, activation of such tumor suppressor pathways must be restricted only by oncogenic, not normal, growth signals. Using a novel in vivo model of Myc-induced tumorigenesis in which Myc function is deregulated without concomitant over-expression, we show that tumor surveillance programs are triggered specifically by Myc over-expression, not deregulation. Nonetheless, low-level deregulated Myc remains potently oncogenic. These observations identify a novel mechanism by which the tumor suppressor defense mechanisms can be circumvented, with implications for our understanding of early stage neoplasia.